A hybrid T-type (HT-type) multilevel inverter with reduced components - Meraj, S.T. (Ain Shams University, 2021)
This paper introduces a new HT-type module for both symmetrical and asymmetrical multilevel inverters (MLIs) with reduced power electric components. The proposed module comprises of two back to back T-type inverters connected with four cross-connected switches. This MLI addresses two major drawbacks associated with the conventional and other recently proposed MLIs which are the high voltage stress of switches and higher power component counts. The structure of the proposed device is designed combining the beneficial features of both T-type inverter and cross-switched inverter. The 1st feature allows the module to produce negative voltage levels deprived of any extra H-bridge circuit and thus decreasing the overall voltage stress significantly. The latter feature allows the device to utilize reduced number of switches to produce higher voltage levels. A comprehensive comparative analysis is additionally established between other MLI topologies to confirm the superiority of the HT-type MLI. From this analysis, it is found that the proposed MLI has successfully overcome the issues associated with other MLIs, it was able to produce the results following industrial standards and it outperformed other MLIs in different aspects such as power components count, cost, efficiency and dynamic performance. Selective harmonic elimination pulse width modulation (SHE-PWM) and nearest level control (NLC) algorithm is considered in this manuscript to generate the output results from the proposed HT-type module. All the details about the operating principle and modulation techniques utilized for the proposed MLI module are stated and validated by both simulation and experimental results. Â© 2020 Faculty of Engineering, Ain Shams University